Assessing cardiovascular disease risk factors in underserved young adult populations - Opoku-Acheampong, Audrey Anima (Kansas State University, 2022)
Cardiovascular disease (CVD, i.e., disease of the heart and blood vessels) is a major cause of death in the United States and globally. Despite the importance of CVD risk assessment for effective CVD prevention intervention, current assessment tools use either clinical or non-clinical factors alone or in combination to assess disease risk(s). However, in limited-resource or underserved communities, where members have less or no health insurance coverage; higher cost barriers to health care access; and poor self-rated general health, disease diagnoses with such clinical tools may be elusive. Additionally, understanding people’s motivation to participate in health-promoting behaviors is essential for the maintenance and improvement of health. The primary aim of this study was to develop a non-clinical-based survey instrument to be used to identify or assess CVD risks in underserved young adult populations. The study’s specific objectives were to: (1) conduct a systematic literature review to critically appraise and summarize existing CVD risk assessment tools; and (2) adapt or develop a new instrument, incorporating a behavioral component into it, and pilot-test it among young adults from underserved populations. Two online electronic databases – PubMed and Scopus – were searched to identify existing risk assessment tools available in English only and published between 2008 and 2019. A total of 21 distinct CVD risk assessment tools were identified; six of these did not require clinical or laboratory data in their estimation (i.e., were non-clinical). Development of the new instrument, Need-2-Know CVD risk assessment questionnaire, occurred in three phases: focus group discussion (FGD); instrument development, and test-retest reliability testing of questionnaire. The final Need-2-Know CVD risk assessment questionnaire comprised a total of 59 items assessing behavioral risk factors (tobacco use, alcohol consumption, diet, and physical activity), basic psychological needs satisfaction, personal medical history, type of health insurance, and demographic data. Test-retest correlation coefficients ranged from 0.037 to 0.736 for items in the Tobacco use subscale; 0.471 to 1.000 for the Alcohol use items; 0.337 to 0.664 for Diet items; 0.098 to 0.726 for PA items; and 0.601 to 0.724 for the psychological needs satisfaction. Even though most of the correlation coefficients for Diet and PA subscales were significant, they showed unacceptable to poor reliability. To the best of our knowledge, the systematic review conducted as part of this study is the first to identify tools or instruments that have been used to assess CVD risk factors in the young adult population. The items on the subscales of the Need-2-Know CVD risk questionnaire showed acceptable consistency across items. However, the questionnaire showed unacceptable to poor reliability. That notwithstanding, the Need-2-Kow CVD risk assessment questionnaire can be a valuable tool for assessing CVD risks among young adults in a non-clinical and public health settings.
Keywords: Non-clinical; Risk assessment; Underserved; Young adult; Chronic disease; Instrument